2002
DOI: 10.1262/jrd.48.183
|View full text |Cite
|
Sign up to set email alerts
|

The Arcuate Nucleus Mediates Facilitating Effect of Estrogen on Glutamate-Induced In Vitro GnRH Release from Nerve Terminals of Female Rats.

Abstract: Abstract. It is well accepted that glutamate stimulates in vivo and in vitro gonadotropin-releasing hormone (GnRH) and/or luteinizing hormone (LH) release. The present study aimed to determine whether the arcuate nucleus (ARC) has a role in exerting the modulating effect of estrogen on GnRH response to glutamate. The effects of estrogen on glutamate-induced in vitro GnRH release from either the ARC-median eminence (ME) or ME fragment were examined in female rats. Both high and low doses of estradiol-17β treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition to AVPV kisspeptin neurons, ARC kisspeptin neurons may mediate the effect of GnRH(1-5) challenge to enhance the surgelike increase in LH release. Involvement of ARC kisspeptin neurons and hypothalamic glutamatergic neurons in GnRH/LH surge generation has been suggested as follows: an increase in c-Fos expressions in the ARC kisspeptin neurons was shown prior to GnRH/LH surge in rats [24] and ewe [25,26]; female rats with attenuated ARC kisspeptin neurons by neurotoxin showed limited magnitude of LH surge [27]; an increase in in vivo glutamate release prior to LH surge is evident in the medio-basal hypothalamus including the ARC in female rats [28]; glutamate strongly stimulated in vitro GnRH release from the ARC-median eminence fragment of female rats, but the stimulating effect was moderate with the fragment without the ARC [29]. In rodents, it is considered that majority of ARC kisspeptin neurons are glutamatergic ones as well, because nearly 90% of ARC kisspeptin neurons expressed glutamate transporter mRNA in mice [30].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to AVPV kisspeptin neurons, ARC kisspeptin neurons may mediate the effect of GnRH(1-5) challenge to enhance the surgelike increase in LH release. Involvement of ARC kisspeptin neurons and hypothalamic glutamatergic neurons in GnRH/LH surge generation has been suggested as follows: an increase in c-Fos expressions in the ARC kisspeptin neurons was shown prior to GnRH/LH surge in rats [24] and ewe [25,26]; female rats with attenuated ARC kisspeptin neurons by neurotoxin showed limited magnitude of LH surge [27]; an increase in in vivo glutamate release prior to LH surge is evident in the medio-basal hypothalamus including the ARC in female rats [28]; glutamate strongly stimulated in vitro GnRH release from the ARC-median eminence fragment of female rats, but the stimulating effect was moderate with the fragment without the ARC [29]. In rodents, it is considered that majority of ARC kisspeptin neurons are glutamatergic ones as well, because nearly 90% of ARC kisspeptin neurons expressed glutamate transporter mRNA in mice [30].…”
Section: Discussionmentioning
confidence: 98%
“…We determined whether kisspeptin mediates the effects of several stimulatory neurotransmitters on LH release. The effects of peripheral injection of monosodium glutamate (MSG), an excitatory amino acid, on LH secretion were determined because NMDA, kainate and AMPA stimulated GnRH release from the cultured median eminence and/or ARC‐median eminence tissue . Because the median eminence is out of the blood–brain barrier, MSG was administered intravenously.…”
Section: Methodsmentioning
confidence: 99%
“…N-methyl-D-aspartate (NMDA), an ionotropic glutamatergic receptor agonist, immediately stimulates LH secretion in wild-type female rats but not in Kiss1 knockout rats [ 21 ]. Furthermore, our previous studies have revealed that the expression of NR1 gene ( Grin1 ), a subunit of the NMDA receptor, can be observed in most ARC kisspeptin neurons in female rats [ 22 ], and glutamate treatment largely enhanced in vitro GnRH release from the ARC-median eminence tissue taken from female rats [ 23 ]. Notably, previous studies have indicated the suppressive effect of SST-SSTR2 signaling on glutamate release from glutamatergic neurons in the cerebral cortex and retina of mice [ 24 , 25 ] and in the hippocampus and basal forebrain of rats [ 26 , 27 ].…”
mentioning
confidence: 99%